Discovery and characterization of single-domain antibodies for polymeric Ig receptor-mediated mucosal delivery of biologics. Issue 1 (1st January 2020) - Maruthachalam, Bharathikumar Vellalore; Zwolak, Adam; Lin-Schmidt, Xiefan; Keough, Edward; Tamot, Ninkka; Venkataramani, Sathya; Geist, Brian; Singh, Sanjaya; Ganesan, Rajkumar
ABSTRACT: Mucosal immunity is dominated by secretory IgA and IgM, although these are less favorable compared to IgG molecules for therapeutic development. Polymeric IgA and IgM are actively transported across the epithelial barrier via engagement of the polymeric Ig receptor (pIgR), but IgG molecules lack a lumen-targeted active transport mechanism, resulting in poor biodistribution of IgG therapeutics in mucosal tissues. In this work, we describe the discovery and characterization of single-domain antibodies (VHH) that engage pIgR and undergo transepithelial transport across the mucosal epithelium. The anti-pIgR VHH panel displayed a broad range of biophysical characteristics, epitope diversity, IgA competition profiles and transcytosis activity in cell and human primary lung tissue models. Making use of this diverse VHH panel, we studied the relationship between biophysical and functional properties of anti-pIgR binders targeting different domains and epitopes of pIgR. These VHH molecules will serve as excellent tools for studying pIgR-mediated transport of biologics and for delivering multispecific IgG antibodies into mucosal lumen, where they can target and neutralize mucosal antigens.